The Effect of Melinjo Peel Extract in Activity of Lipoprotein Lipase Enzym of The Rats Fed a Hypercholesterolemia Diet - Demitri, Athira (Universitas Wijaya Kusuma Surabaya, 2018)
The intake of saturated fat and cholesterol that comes from food digested in the intestine resulting in free fatty acids, triglycerides, phospholipids, and cholesterol. Triglyceride levels increased can be caused by presence of impaired lipoprotein lipase (LPL) enzyme activity. LPL activity can be increased by flavonoid in plant, like Melinjo peel. The purpose of this study is to measure LPL enzyme activity before and after being given extract of Melinjo peel treatment. This research use true experimental, with study design of pretest posttest control group design. Hypercholesterolemic diet given to rats by oral gavage as much as 1,8 grams for 14 days. Melinjo peel extract were given by oral gavage for 14 days after the hypercholesterolemic diet is given. Statistical analysis used Paired Sample T-Test to compare lipoprotein lipase activity before and after treatment. Then, used MANOVA (Multivariate Analyses of Variance) to see the difference of lipoprotein lipase activity in each group after treatment.Based on statistical analysis showed that there were differences of lipoprotein lipase activity in the hypercholesterolemic diet group, HD+54.15, HD+108.30, and HD+216.60 before and after treatment significant (p. < 0.05). The activity of lipoprotein lipase in the normal diet group compared with the hypercholesterolemic and HD+216.60 group showed a significant difference (p. < 0.05). Melinjo peel extract can increased activity of lipoprotein lipase enzym after treatment, those can be due to the flavonoid in Melinjo peel extract.